2002
DOI: 10.1081/clt-120016955
|View full text |Cite
|
Sign up to set email alerts
|

Severe Propanil [N-(3,4-Dichlorophenyl) Propanamide] Pesticide Self-Poisoning

Abstract: Background-propanil pesticide poisoning can produce methaemoglobinaemia, tissue hypoxia, and depression of CNS and respiratory system. It has been recorded only rarely worldwide and most current poison texts consider propanil to be of low toxicity. However, propanil selfpoisoning is a significant clinical problem in parts of Sri Lanka and a not uncommon cause of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…However, such limitations are the norm throughout the developing world. For example, propanil's case fatality of 11% is unexpectedly high for an agent whose toxicity is largely due to methaemoglobinaemia and haemolysis, complications that should be relatively easily treated [24]. However, the difficulty in monitoring treatment response without cooximeters and problems with access to and dose adjustment of the antidote have all been suggested as major contributory causes to the high case fatality [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such limitations are the norm throughout the developing world. For example, propanil's case fatality of 11% is unexpectedly high for an agent whose toxicity is largely due to methaemoglobinaemia and haemolysis, complications that should be relatively easily treated [24]. However, the difficulty in monitoring treatment response without cooximeters and problems with access to and dose adjustment of the antidote have all been suggested as major contributory causes to the high case fatality [24].…”
Section: Discussionmentioning
confidence: 99%
“…For example, propanil's case fatality of 11% is unexpectedly high for an agent whose toxicity is largely due to methaemoglobinaemia and haemolysis, complications that should be relatively easily treated [24]. However, the difficulty in monitoring treatment response without cooximeters and problems with access to and dose adjustment of the antidote have all been suggested as major contributory causes to the high case fatality [24]. Previous studies have also documented high complication rates from gastrointestinal decontamination in rural hospitals that may increase mortality [25].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have shown some amounts of these agrochemicals to be present in water in small quantities (except phosphate in higher quantities in reservoir water) some of the affected areas [4,30,68,69], but no data exist indicating that any of these chemicals directly causing CKD-mfo [86][87][88]. In addition, these chemicals are used not only in the CKD-affected areas, but also throughout Sri Lanka and, in fact, globally.…”
Section: Agrochemical (Pesticides and Weedicides) Contaminationmentioning
confidence: 99%
“…Long-term exposure to high concentrations of propanil, chlorpyrifos, and glyphosate may cause various chronic diseases, predominantly neurological disorders, endocrine disruptions, liver disease, and CKD [68][69][70], but the pattern of the renal disease following exposure to these is quite different from that of CKD-mfo. On the other hand, some of the recently introduced pesticides, such as neonicotinoids, incorporate into plants and crops and thus directly contaminate the food chain.…”
Section: Agrochemical (Pesticides and Weedicides) Contaminationmentioning
confidence: 99%
“…Animal studies that have suggested that the kidney might be a target for propanil did not investigate the role of metabolites (Ambrose et al, 1972). Evidence for propanil-induced nephrotoxicity from human studies comes from case reports where renal function data are not always presented and little evidence of blood levels of propanil or its metabolites are available to calculate organ exposure (Wijekoon et al, 1974; De Silva and Bodinayake, 1997; Yamazaki et al, 2001; Eddleston et al, 2002). Thus, in humans, where propanil nephrotoxicity has been detected, the human studies have not examined the role of propanil metabolites in propanil nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%